SOCIAL-HISTORICAL BASICS OF THE DEVELOPMENT OF ECOLOGICAL - VALEOLOGICAL CULTURE IN FUTURE PRIMARY CLASS TEACHERS (Conference Zone, 2022)
This article discusses the unity and interdependence of human genesis, ontogenesis and phylogenesis, anthropogenesis and systemogenesis, philosophical anthropology and cultural (social) anthropology and pedagogical anthropology.